2012
DOI: 10.1186/1746-6148-8-223
|View full text |Cite
|
Sign up to set email alerts
|

In vitro amplification of ovine prions from scrapie-infected sheep from Great Britain reveals distinct patterns of propagation

Abstract: BackgroundProtein misfolding cyclic amplification (PMCA) is a method that facilitates the detection of prions from many sources of transmissible spongiform encephalopathy (TSE). Sheep scrapie represents a unique diversity of prion disease agents in a range of susceptible PRNP genotypes. In this study PMCA was assessed on a range of Great Britain (GB) sheep scrapie isolates to determine the applicability to veterinary diagnosis of ovine TSE.ResultsPrPSc amplification by protein misfolding cyclic amplification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Increased surveillance efforts during the past several years have led to the detection of new cases in U.S. states previously thought to be outside the area where CWD is endemic (e.g., Texas, Iowa, and Pennsylvania in 2012 and Ohio in 2014) (9)(10)(11). As this devastatingly fatal disease spreads across the United States and beyond, the importance of highly sensitive antemortem detection becomes increasingly evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased surveillance efforts during the past several years have led to the detection of new cases in U.S. states previously thought to be outside the area where CWD is endemic (e.g., Texas, Iowa, and Pennsylvania in 2012 and Ohio in 2014) (9)(10)(11). As this devastatingly fatal disease spreads across the United States and beyond, the importance of highly sensitive antemortem detection becomes increasingly evident.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has since been documented in 23 U.S. states, 2 Canadian provinces, and, via exportation of farmed cervids, the Republic of Korea (5)(6)(7)(8). Four of the 23 states (Texas, Iowa, Pennsylvania, and Ohio) were considered CWD free prior to 2012, with primary cases in three of these states reportedly arising in farmed cervids (9)(10)(11). With the movement of cervids across state and national borders, these new epidemic foci illustrate the increased need for highly sensitive surveillance methods and appropriate antemortem tissue collection in order to potentially mitigate both natural and anthropogenic spread and more accurately estimate prevalence.…”
mentioning
confidence: 99%
“…It is generally accepted that prion protein conversion studies, similar to transgenic-mouse studies, resemble the trend of incubation periods in intracerebral inoculations, and that for sheep (and some other species) they also seem to be biologically relevant for oral and natural transmission routes (61,62). Even though PrP Sc accumulation in the brain is considered the prime indicator for successful TSE agent spread, other peripheral organs like the liver, spleen, and gut can also significantly contribute to agent spread (2,59,63).…”
Section: Discussionmentioning
confidence: 99%
“…The newly generated PrP Sc produced in homologous conversion assays shares the same biochemical, biological and structural properties as the parental isolate (Castilla et al, 2008a;Green et al, 2008;Thorne et al, 2012;Vidal et al, 2013a;Levavasseur et al, 2014;Priem et al, 2014), although exceptions have been reported . This reproduction of strain adaptation and molecular patterns indicate again that the strain determinants are largely encoded in the structure and folding of PrP Sc (Castilla et al, 2008a).…”
Section: Pmca Was Developed In 2001 As a Technique For The In Vitro Amentioning
confidence: 95%
“…As seen in vivo the strain and source of PrP Sc , in particular the PRNP genotype of seed and substrate, has a clear influence on the amplification pattern obtained by PMCA (Bucalossi et al, 2011;Thorne et al, 2012;Krejciova et al, 2014;Priem et al, 2014). In this regard it is of interest that a switch of the conversion profile has been shown by the amplification of an ARR scrapie isolate in different sheep genotypes, which resulted in a conversion profile that resembled mostly that of ARQ scrapie (Bucalossi et al, 2011;Priem et al, 2014).…”
Section: Pmca Was Developed In 2001 As a Technique For The In Vitro Amentioning
confidence: 99%